Recent social trends in the United States. Report of the President's Research Committee on social trends. With a forew. by H. Hoover. [With contribs of W.S. Thompson, P.K. Whelpton, F.G. Tryon a.o.] (Mcgraw-Hill, 1933)
With graphs, ills, index and tabs.